Preparation method of hard carbon negative electrode material of capacity type sodium-ion battery

Through vacuum impregnation and low-temperature carbonization technology, low-cost and high-capacity hard carbon negative electrode materials are prepared, which solves the problems of high production costs and low capacity of existing hard carbon negative electrode materials, and improves the energy density and commercialization potential of sodium ion batteries. .

CN119503767APending Publication Date: 2025-02-25SHENZHEN JANAENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411603383.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The production cost of existing hard carbon anode materials is high and the capacity is relatively low, which limits the energy density and commercial development of sodium ion batteries.

Method used

Through vacuum impregnation and low-temperature carbonization technology, low-cost and high-capacity hard carbon negative electrode materials are prepared. Specific steps include raw material pretreatment, vacuum impregnation, low-temperature carbonization, crushing and refining and high-temperature carbonization.

Benefits of technology

It has achieved low production costs, high capacity and good graphitization of hard carbon negative electrode materials, which has improved the energy density and commercialization potential of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a capacity type sodium ion battery hard carbon negative electrode material, which comprises the following steps: S1, raw material pretreatment: crushing, sieving and drying a hard carbon raw material to obtain a precursor raw material; s2, raw material impregnation: impregnating the precursor raw material obtained in the step S1 in a vacuum impregnation tank to obtain an impregnated raw material; s3, low-temperature carbonization: carrying out low-temperature carbonization on the impregnated raw material in a protective atmosphere to obtain a low-temperature carbonized material; s4, crushing and refining: crushing and refining the low-temperature carbonized material obtained in the step S3 to obtain a refined low-temperature carbonized material; and S5, performing high-temperature carbonization: performing high-temperature carbonization on the refined low-temperature carbonized material obtained in the step S4 in a protective atmosphere to obtain a finished product of the hard carbon negative electrode material. The preparation method of the hard carbon negative electrode material of the capacity type sodium-ion battery has the characteristics of low cost, high capacity and good graphitization degree.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery. Background Art

[0002] Compared with lithium-ion batteries, which are resource-constrained, sodium-ion batteries have a wide distribution of resources, abundant reserves, and low raw material costs, so they have greater development potential in the field of large-scale energy storage in the future. For sodium-ion batteries, the development of high-performance, low-cost positive and negative electrode materials is the key to their commercial application.

[0003] At present, the negative electrode materials of sodium ion batteries include hard carbon, soft carbon, alloys, organic matter, etc. Among them, hard carbon negative electrode materials are highly favored due to their rich resources, wide sources, low cost, high sodium storage capacity, low sodium storage potential, and good cycle stability.

[0004] However, the production cost of existing hard carbon negative electrode materials is relatively high, and they cannot show a price advantage compared with lithium-ion batteries. On the other hand, the capacity of hard carbon materials is relatively low, resulting in a relatively low energy density of sodium-ion batteries. These two limitations have hindered the commercial development of sodium-ion batteries. One of the reasons for the high production cost of hard carbon materials is their high carbonization temperature. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a capacity-type sodium ion battery hard carbon negative electrode material, which has the characteristics of low cost, high capacity and good graphitization degree.

[0006] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crushing, sieving and drying the hard carbon raw material to obtain a precursor raw material; S2, raw material impregnation: impregnating the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material; S3, low temperature carbonization: low temperature carbonization of the impregnated raw material under a protective atmosphere to obtain a low temperature carbonized material; S4, crushing and refining: crushing and refining the low-temperature carbonized material obtained in step S3 to obtain refined low-temperature carbonized material; S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material.

[0007] Furthermore, in step S2, the process of vacuum impregnation is as follows: placing the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuating the tank to maintain the vacuum and injecting the impregnation liquid to maintain the pressure, then releasing the pressure, discharging the impregnation liquid, opening the tank to take out the impregnated material, and dehydrating it by centrifugation and / or filtration; in step S2, compared with other mixing methods, the vacuum impregnation method allows the impregnating agent to better penetrate into the interior of the raw material, thereby making the subsequent reaction more uniform and reducing the amount of dehydrating agent used.

[0008] Furthermore, in step S2, the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of the dehydrating agent added is 10-30% of the mass of the precursor raw material, and the amount of water used is 5-10 times the mass of the precursor raw material; the amount of the dehydrating agent added affects the effect of the present invention: if the amount of the dehydrating agent added is too low, the dehydration effect in step S3 is poor, and the purpose of dehydration promoting carbonization cannot be achieved; if the amount of the dehydrating agent added is too high, the degree of carbonization is too high, which also affects the effect of the present invention.

[0009] Furthermore, the dehydrating agent is one or more of sulfuric acid, nitric acid, phosphoric acid, and chlorine sulfate, and the impregnation liquid is a reusable impregnation liquid. Before each reuse, the dehydrating agent is appropriately supplemented to a required concentration according to the concentration of the impregnation liquid.

[0010] Furthermore, in step S2, the vacuum degree is 1-100 kPa, and the pressure holding time is 2-10 hours; when vacuuming, part of the air in the raw material is also extracted, and the resistance of the impregnation liquid to penetrate into the pores of the raw material is reduced, making it easier to penetrate into the interior of the raw material. Therefore, the lower the vacuum degree, the better the effect of the present invention; but too low a vacuum degree puts higher requirements on the sealing of the equipment, the capacity of the vacuum pump, and the vacuuming time, and increases the production cost.

[0011] Further, in step S3, the low-temperature carbonization includes a first stage and a second stage, and the protective atmosphere is nitrogen and / or argon; the first stage is low-temperature baking to remove water (free water), and its carbonization conditions are: temperature 150-250°C, insulation time 1-5h; the second stage is low-temperature carbonization, and its carbonization temperature is 350-700°C and insulation time is 2-5h.

[0012] In the second stage of carbonization, some oxygen-containing functional groups in the precursor material, such as hydroxyl, carboxyl, and ether bonds, undergo dehydration reactions under the action of the dehydrating agent, so that heteroatoms such as H and O can be volatilized and released at a lower temperature, and double bonds are formed between two adjacent carbon atoms.

[0013] The specific mechanism of the reaction of the entire step S3 is as follows: the carboxyl group has poor thermal stability and is pyrolyzed to form a hydroxyl group in the process. The ether group undergoes a ring-opening reaction after protonation under the action of Lewis acid to form a hydroxyl group. In the absence of a catalyst, the hydroxyl group requires a higher reaction temperature (generally >1000°C) to be thermally released. Under the action of a dehydrating agent, the hydroxyl group undergoes a dehydration reaction and forms a double bond between two adjacent carbon atoms. In this reaction, not only can O and H heteroatoms be removed, but also a CC double bond can be constructed. The CC double bond of SP2 is easier to form a graphitized structure than the single bond of SP3, which makes it easier for the carbon material to form a complete carbon layer structure during the subsequent high-temperature carbonization process.

[0014] At the same time, it should be noted that during step S3, the carbonization temperature will affect the effect of the present invention: if the reaction temperature is too low, the dehydration reaction is difficult to occur and the effect of the present invention cannot be achieved; if the reaction temperature is too high, the dehydrating agent is easy to decompose and the effect of the present invention cannot be achieved.

[0015] Further, in step S5, the high temperature carbonization conditions are: the protective atmosphere is nitrogen and / or argon, the heating rate is 0.5-5°C / min, the carbonization temperature is 900-1200°C, and the carbonization time is 2-5 h.

[0016] Furthermore, in step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

[0017] Furthermore, in step S1, the precursor raw material is dried to a moisture content of ≤3%; and crushed and sieved, with a mesh size of ≤1 cm. If the moisture content is too high or the size is too large, then in step S2, the impregnation liquid is not easy to penetrate into the pores of the raw material, affecting the effect of the present invention.

[0018] Furthermore, in step S4, the pulverizing method is one or more of roller mill, mechanical mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the fineness of the low-temperature carbonized material must meet the D50 of 5-20 μm.

[0019] The present invention provides a method for preparing a capacity-type sodium ion battery hard carbon negative electrode material, which has the following beneficial effects: First, the production cost is low. Under the action of the dehydrating agent, the hydroxyl groups in the precursor material undergo a dehydration reaction and form a double bond between two adjacent carbon atoms, so that the carbon material can form a complete carbon layer structure at a lower temperature, thereby reducing the production cost.

[0020] Second, the capacity is high. The dehydrating agent enables the carbon material to form a complete carbon layer structure, ensuring more sodium storage active sites (between carbon layers), thereby increasing the sodium storage capacity and effectively ensuring that it has a higher gram capacity when used as a sodium ion negative electrode material.

[0021] Third, the degree of graphitization is high. By combining raw material impregnation with low-temperature carbonization, the reaction uniformity is ensured, the influence of moisture on the subsequent high-temperature carbonization process is reduced, and the degree of graphitization of the obtained negative electrode material is effectively improved. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0023] The present invention discloses a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crushing, sieving and drying the hard carbon raw material to obtain a precursor raw material; S2, raw material impregnation: impregnating the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material; S3, low temperature carbonization: low temperature carbonization of the impregnated raw material under a protective atmosphere to obtain a low temperature carbonized material; S4, crushing and refining: crushing and refining the low-temperature carbonized material obtained in step S3 to obtain refined low-temperature carbonized material; S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material.

[0024] Furthermore, in step S2, the process of vacuum impregnation is as follows: placing the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuating the tank to maintain the vacuum and injecting the impregnation liquid to maintain the pressure, then releasing the pressure, discharging the impregnation liquid, opening the tank to take out the impregnated material, and dehydrating it by centrifugation and / or filter pressing.

[0025] Furthermore, in step S2, the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of the dehydrating agent added is 10-30% of the mass of the precursor raw material, and the amount of water used is 5-10 times the mass of the precursor raw material.

[0026] Furthermore, the dehydrating agent is one or more of sulfuric acid, nitric acid, phosphoric acid and chlorine sulfate, and the impregnating liquid is a reusable impregnating liquid.

[0027] Furthermore, in step S2, the vacuum degree is 1-100 kPa, and the pressure holding time is 2-10 hours.

[0028] Further, in step S3, low-temperature carbonization includes a first stage and a second stage, and the protective atmosphere is nitrogen and / or argon; the carbonization conditions in the first stage are: temperature 150-250°C, insulation time 1-5h; the carbonization temperature in the second stage is 350-700°C, insulation time 2-5h.

[0029] Further, in step S5, the high temperature carbonization conditions are: the protective atmosphere is nitrogen and / or argon, the heating rate is 0.5-5°C / min, the carbonization temperature is 900-1200°C, and the carbonization time is 2-5 h.

[0030] Furthermore, in step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

[0031] Furthermore, in step S1, the precursor raw material is dried to make the moisture content ≤3%; and crushed and sieved, with the mesh size ≤1 cm.

[0032] Furthermore, in step S4, the pulverizing method is one or more of roller mill, mechanical mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the fineness of the low-temperature carbonized material must meet the D50 of 5-20 μm.

[0033] Example 1 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crushing, sieving and drying the hard carbon raw material to obtain a precursor raw material. Specifically, the hard carbon raw material is walnut shells and nut shells; drying to make the moisture content of the precursor raw material ≤3%; crushing and sieving, and the mesh size of the sieve is ≤1cm.

[0034] S2, raw material impregnation: impregnate the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material. Specifically, the process of vacuum impregnation is: place the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuate to maintain vacuum and inject impregnation liquid to maintain pressure, then release the pressure, discharge the impregnation liquid, open the tank to take out the impregnated material, and dehydrate it by centrifugation; the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of dehydrating agent added is 30% of the mass of the precursor raw material, and the amount of water used is 8 times the mass of the precursor raw material; the dehydrating agent is sulfuric acid or nitric acid, and the impregnation liquid is a reused impregnation liquid; the vacuum degree is 5kPa, and the pressure holding time is 10h.

[0035] S3, low temperature carbonization: low temperature carbonization of the impregnated raw materials under protective atmosphere to obtain low temperature carbonized materials. Specifically, low temperature carbonization includes the first stage and the second stage, the protective atmosphere is nitrogen gas; the first stage carbonization conditions are: temperature 200 ° C, insulation time 1h; the second stage carbonization temperature 700 ° C, insulation time 3.5h.

[0036] S4, crushing and refining: crushing and refining the low temperature carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is double roller and mechanical grinding; the fineness of the low temperature carbonized material needs to meet the D50 of 5-20 μm.

[0037] S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material. Specifically, the conditions for high temperature carbonization are: the protective atmosphere is or argon, the heating rate is 0.5 ℃ / min, the carbonization temperature is 1200 ℃, and the carbonization time is 3.5 h.

[0038] Example 2 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crush, sieve and dry the hard carbon raw material to obtain a precursor raw material. Specifically, the hard carbon raw material is coffee shell, coconut shell, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, lignite, sub-bituminous coal; dry the precursor raw material to a moisture content of ≤3%; crush and sieve, the mesh size of the sieve is ≤1cm.

[0039] S2, raw material impregnation: impregnate the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnation raw material. Specifically, the process of vacuum impregnation is: place the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuate to maintain vacuum and inject impregnation liquid to maintain pressure, then release the pressure, discharge the impregnation liquid, open the tank to take out the impregnation material, and dehydrate it by filter pressing; the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of dehydrating agent added is 20% of the mass of the precursor raw material, and the amount of water used is 5 times the mass of the precursor raw material; the dehydrating agent is phosphoric acid and sulfuric acid, and the impregnation liquid is a reused impregnation liquid; the vacuum degree is 100 kPa, and the pressure holding time is 5h.

[0040] S3, low temperature carbonization: low temperature carbonization of the impregnated raw materials under protective atmosphere to obtain low temperature carbonized materials. Specifically, low temperature carbonization includes the first stage and the second stage, the protective atmosphere is argon; the first stage carbonization conditions are: temperature 150°C, insulation time 5h; the second stage carbonization temperature 550°C, insulation time 2h.

[0041] S4, pulverizing and refining: pulverizing and refining the low temperature carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the pulverizing method is air flow powder and ball milling; the fineness of the low temperature carbonized material needs to meet the D50 of 5-20 μm.

[0042] S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material. Specifically, the high temperature carbonization conditions are: the protective atmosphere is nitrogen, the heating rate is 5 °C / min, the carbonization temperature is 1100 °C, and the carbonization time is 2 h.

[0043] Example 3 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crush, sieve and dry the hard carbon raw material to obtain a precursor raw material. Specifically, the hard carbon raw material is walnut shell, nut shell, coconut shell, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak and anthracite; dry the precursor raw material to a moisture content of ≤3%; crush and sieve, and the mesh size is ≤1cm.

[0044] S2, raw material impregnation: impregnate the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material. Specifically, the process of vacuum impregnation is: place the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuate to maintain vacuum and inject impregnation liquid to maintain pressure, then release the pressure, discharge the impregnation liquid, open the tank to take out the impregnated material, and dehydrate it by centrifugation and filter pressing; the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of dehydrating agent added is 10% of the mass of the precursor raw material, and the amount of water used is 10 times the mass of the precursor raw material; the dehydrating agent is sulfuric acid, nitric acid, phosphoric acid, and the impregnation liquid is a reused impregnation liquid; the vacuum degree is 50 kPa, and the pressure holding time is 2h.

[0045] S3, low temperature carbonization: low temperature carbonization of the impregnated raw materials under protective atmosphere to obtain low temperature carbonized materials. Specifically, low temperature carbonization includes the first stage and the second stage, the protective atmosphere is nitrogen and argon; the first stage carbonization conditions are: temperature 250°C, insulation time 3h; the second stage carbonization temperature 700°C, insulation time 5h.

[0046] S4, crushing and refining: crushing and refining the low temperature carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is ball milling and sand milling; the fineness of the low temperature carbonized material needs to meet the D50 of 5-20 μm.

[0047] S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material. Specifically, the high temperature carbonization conditions are: the protective atmosphere is nitrogen and argon, the heating rate is 0.5°C / min, the carbonization temperature is 1200°C, and the carbonization time is 3.5 h.

[0048] Example 4 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crush, sieve and dry the hard carbon raw material to obtain a precursor raw material. Specifically, the hard carbon raw material is straw, reed, coffee shell, coconut shell, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir and oak; dry the precursor raw material to a moisture content of ≤3%; crush and sieve, and the mesh size is ≤1cm.

[0049] S2, raw material impregnation: impregnate the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material. Specifically, the process of vacuum impregnation is: place the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuate to maintain vacuum and inject impregnation liquid to maintain pressure, then release the pressure, discharge the impregnation liquid, open the tank to take out the impregnated material, and dehydrate it by centrifugation and filter pressing; the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of dehydrating agent added is 14% of the mass of the precursor raw material, and the amount of water used is 6 times the mass of the precursor raw material; the dehydrating agent is sulfuric acid, nitric acid, phosphoric acid, and the impregnation liquid is a reused impregnation liquid; the vacuum degree is 30 kPa, and the pressure holding time is 4h.

[0050] S3, low temperature carbonization: low temperature carbonization of the impregnated raw materials under protective atmosphere to obtain low temperature carbonized materials. Specifically, low temperature carbonization includes the first stage and the second stage, the protective atmosphere is nitrogen and argon; the first stage carbonization conditions are: temperature 180°C, insulation time 4h; the second stage carbonization temperature 600°C, insulation time 4h.

[0051] S4, crushing and refining: crushing and refining the low temperature carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is sand grinding; the fineness of the low temperature carbonized material needs to meet D50 of 5-20 μm.

[0052] S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material. Specifically, the high temperature carbonization conditions are: the protective atmosphere is nitrogen and / or argon, the heating rate is 1°C / min, the carbonization temperature is 1000°C, and the carbonization time is 3 hours.

[0053] Example 5 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: crushing, sieving and drying the hard carbon raw material to obtain a precursor raw material. Specifically, the hard carbon raw material is walnut shell, nut shell, apricot shell, straw, reed, coffee shell, coconut shell; drying to make the moisture content of the precursor raw material ≤3%; crushing and sieving, the mesh size of the sieve is ≤1cm.

[0054] S2, raw material impregnation: impregnate the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material. Specifically, the process of vacuum impregnation is: place the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuate to maintain vacuum and inject impregnation liquid to maintain pressure, then release the pressure, discharge the impregnation liquid, open the tank to take out the impregnated material, and dehydrate it by centrifugation and filter pressing; the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of dehydrating agent added is 22% of the mass of the precursor raw material, and the amount of water used is 7 times the mass of the precursor raw material; the dehydrating agent is sulfuric acid, nitric acid, phosphoric acid, and chlorine sulfate, and the impregnation liquid is a reused impregnation liquid; the vacuum degree is 80 kPa, and the pressure holding time is 4h.

[0055] S3, low temperature carbonization: low temperature carbonization of the impregnated raw materials under protective atmosphere to obtain low temperature carbonized materials. Specifically, low temperature carbonization includes the first stage and the second stage, the protective atmosphere is nitrogen and argon; the first stage carbonization conditions are: temperature 220°C, insulation time 2h; the second stage carbonization temperature 400°C, insulation time 3h.

[0056] S4, crushing and refining: crushing and refining the low temperature carbonized material obtained in step S3 to obtain refined low temperature carbonized material. Specifically, the crushing method is ball milling and stirring milling; the fineness of the low temperature carbonized material needs to meet the D50 of 5-20 μm.

[0057] S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material. Specifically, the high temperature carbonization conditions are: the protective atmosphere is nitrogen and argon, the heating rate is 4°C / min, the carbonization temperature is 1000°C, and the carbonization time is 4 hours.

[0058] Application Example 1 This embodiment relates to a method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, comprising the following steps: S1. Raw material pretreatment: The coconut shell raw material is crushed, sieved and dried to obtain a dry precursor raw material of a certain fineness, with a moisture content of 2% and a sieve aperture of 1 cm.

[0059] S2, raw material impregnation: the coconut shell raw material obtained in step S1 is placed in a vacuum impregnation tank, evacuated to 20 kPa, the vacuum is maintained and the impregnation liquid is injected, the pressure is maintained for 5 hours, and then the pressure is released, the impregnation liquid is discharged, the impregnation raw material is taken out of the tank, and further dehydrated by centrifugation and filter pressing. The dehydrating agent is sulfuric acid, the amount of sulfuric acid added is 25% of the mass of the raw material, and the amount of water used is 6 times the mass of the raw material.

[0060] S3. Low-temperature carbonization: The impregnated raw materials are carbonized at low temperature in a nitrogen atmosphere, firstly heated to 200°C and kept warm for 2 hours, then heated to 600°C and kept warm for 3 hours.

[0061] S4, pulverizing and refining: the low-temperature carbonized material obtained in step S3 is subjected to roller grinding and mechanical grinding to obtain a low-temperature carbonized material with a D50 of 7 μm.

[0062] S5. High-temperature carbonization: The low-temperature carbonized material with a certain fineness obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a carbonization temperature of 1000°C, and a carbonization time of 2.5 h to obtain a finished hard carbon negative electrode material.

[0063] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0064] Comparative Example 1 This embodiment relates to a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Raw material pretreatment: The coconut shell raw material is crushed, sieved and dried to obtain a dry precursor raw material of a certain fineness, with a moisture content of 2% and a sieve aperture of 1 cm.

[0065] S2, raw material impregnation: the coconut shell raw material obtained in step S1 is placed in a vacuum impregnation tank, evacuated to 20 kPa, the vacuum is maintained and the impregnation liquid is injected, the pressure is maintained for 5 hours, and then the pressure is released, the impregnation liquid is discharged, the can is opened to take out the impregnation raw material, and further dehydrated by centrifugation and filter pressing. No dehydrating agent is added, and the amount of water used is 6 times the mass of the raw material.

[0066] S3. Low-temperature carbonization: The impregnated raw materials are carbonized at low temperature in a nitrogen atmosphere, firstly heated to 200°C and kept warm for 2 hours, then heated to 600°C and kept warm for 3 hours.

[0067] S4, pulverizing and refining: the low-temperature carbonized material obtained in step S3 is subjected to roller grinding and mechanical grinding to obtain a low-temperature carbonized material with a D50 of 7 μm.

[0068] S5. High-temperature carbonization: The low-temperature carbonized material with a certain fineness obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a carbonization temperature of 1000°C, and a carbonization time of 2.5 h to obtain a finished hard carbon negative electrode material.

[0069] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0070] Comparative Example 2 This embodiment relates to a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Raw material pretreatment: The coconut shell raw material is crushed, sieved and dried to obtain a dry precursor raw material of a certain fineness, with a moisture content of 2% and a sieve aperture of 1 cm.

[0071] S2, raw material impregnation: the coconut shell raw material obtained in step S1 is placed in a vacuum impregnation tank, evacuated to 20 kPa, the vacuum is maintained and the impregnation liquid is injected, the pressure is maintained for 5 hours, and then the pressure is released, the impregnation liquid is discharged, the can is opened to take out the impregnation raw material, and further dehydrated by centrifugation and filter pressing. No dehydrating agent is added, and the amount of water used is 6 times the mass of the raw material.

[0072] S3. Low-temperature carbonization: The impregnated raw materials are carbonized at low temperature in a nitrogen atmosphere, firstly heated to 200°C and kept warm for 2 hours, then heated to 600°C and kept warm for 3 hours.

[0073] S4, pulverizing and refining: the low-temperature carbonized material obtained in step S3 is subjected to roller grinding and mechanical grinding to obtain a low-temperature carbonized material with a D50 of 7 μm.

[0074] S5. High-temperature carbonization: The low-temperature carbonized material with a certain fineness obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a carbonization temperature of 1300°C, and a carbonization time of 2.5 h to obtain a finished hard carbon negative electrode material.

[0075] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0076] Comparative Example 3 This embodiment relates to a method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: S1. Raw material pretreatment: The coconut shell raw material is crushed, sieved and dried to obtain a dry precursor raw material of a certain fineness, with a moisture content of 2% and a sieve aperture of 1 cm.

[0077] S2, raw material impregnation: the coconut shell raw material obtained in step S1 is placed in a vacuum impregnation tank, evacuated to 20 kPa, the vacuum is maintained and the impregnation liquid is injected, the pressure is maintained for 5 hours, and then the pressure is released, the impregnation liquid is discharged, the can is opened to take out the impregnation raw material, and further dehydrated by centrifugation and filter pressing. No dehydrating agent is added, and the amount of water used is 6 times the mass of the raw material.

[0078] S3. Low-temperature carbonization: The impregnated raw materials are carbonized at low temperature in a nitrogen atmosphere, firstly heated to 200°C and kept warm for 2 hours, then heated to 600°C and kept warm for 3 hours.

[0079] S4, pulverizing and refining: the low-temperature carbonized material obtained in step S3 is subjected to roller grinding and mechanical grinding to obtain a low-temperature carbonized material with a D50 of 7 μm.

[0080] S5. High-temperature carbonization: The low-temperature carbonized material with a certain fineness obtained in step S4 is subjected to high-temperature carbonization in a nitrogen atmosphere at a heating rate of 2°C / min, a carbonization temperature of 1400°C, and a carbonization time of 2.5 h to obtain a finished hard carbon negative electrode material.

[0081] The electrochemical performance of the obtained material was tested according to the following method: hard carbon material, Super P, CMC, SBR were mixed into a slurry at a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine, with metallic sodium as the counter electrode, 1 mol / L NaClO4EC+DEC (1:1 vol%) as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests, with a current density of 0.1C (1C=300 mAh / g) and a voltage range of 2-0.005 V.

[0082] The constant current charge and discharge test measured that the first week charge specific capacity of the hard carbon electrode in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 was 342, 281, 302 and 308 mAh / g. The constant current test results show that the hard carbon material in Example 1 can show a higher capacity at 1000°C, while the hard carbon material in the comparative example needs to be treated at a higher temperature (1300°C, 1400°C) without adding a dehydrating agent to show a high capacity. The reason why the carbonization temperature of Example 1 is significantly reduced and the capacity is significantly increased is that under the action of the dehydrating agent, the hydroxyl group in the precursor material undergoes a dehydration reaction and forms a double bond between two adjacent carbon atoms, so that the carbon material can form a complete carbon layer structure at a lower temperature, thereby reducing the carbonization temperature and increasing the sodium storage active sites.

[0083] Raman measured the Id / Ig values ​​in the Raman spectra of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 to be 2.34, 2.81, 2.65 and 2.43 respectively. The Id / Ig value can be used to indicate the degree of defects and graphitization of the carbon layer of the hard carbon material. Generally, the lower the Id / Ig value, the lower the degree of defects and the higher the degree of graphitization. The Raman test results show that the dehydrating agent enables the hard carbon material to achieve a higher degree of graphitization at a carbonization temperature of 1000°C.

[0084] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery, characterized in that The following steps are involved: S1. Raw material pretreatment: crushing, sieving and drying the hard carbon raw material to obtain a precursor raw material; S2, raw material impregnation: impregnating the precursor raw material obtained in step S1 in a vacuum impregnation tank to obtain an impregnated raw material; S3, low temperature carbonization: low temperature carbonization of the impregnated raw material under a protective atmosphere to obtain a low temperature carbonized material; S4, crushing and refining: crushing and refining the low-temperature carbonized material obtained in step S3 to obtain refined low-temperature carbonized material; S5, high temperature carbonization: the refined low temperature carbonized material obtained in step S4 is subjected to high temperature carbonization under a protective atmosphere to obtain a finished hard carbon negative electrode material.

2. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the process of vacuum impregnation is as follows: placing the precursor raw material obtained in step S1 in a vacuum impregnation tank, evacuating the tank to maintain vacuum and injecting impregnation liquid to maintain pressure, then releasing the pressure, discharging the impregnation liquid, opening the tank to take out the impregnated material, and dehydrating it by centrifugation and / or filter pressing.

3. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the impregnation liquid is an aqueous solution containing a dehydrating agent, the amount of the dehydrating agent added is 10-30% of the mass of the precursor raw material, and the amount of water used is 5-10 times the mass of the precursor raw material.

4. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: The dehydrating agent is one or more of sulfuric acid, nitric acid, phosphoric acid and chlorine sulfate, and the impregnating liquid is a reusable impregnating liquid.

5. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the vacuum degree is 1-100 kPa, and the pressure holding time is 2-10 hours.

6. The method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery according to claim 1, characterized in that: In step S3, low-temperature carbonization includes a first stage and a second stage, and the protective atmosphere is nitrogen and / or argon; the carbonization conditions in the first stage are: temperature 150-250°C, insulation time 1-5h; the carbonization temperature in the second stage is 350-700°C, insulation time 2-5h.

7. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S5, the high-temperature carbonization conditions are: the protective atmosphere is nitrogen and / or argon, the heating rate is 0.5-5°C / min, the carbonization temperature is 900-1200°C, and the carbonization time is 2-5 h.

8. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the hard carbon raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal.

9. The method for preparing a capacity-type sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the precursor raw material is dried to make the moisture content ≤3%; and crushed and sieved, with the mesh size ≤1cm.

10. The method for preparing a hard carbon negative electrode material for a capacity-type sodium ion battery according to claim 1, characterized in that: In step S4, the pulverizing method is one or more of roller mill, mechanical mill, jaw crusher, air flow mill, ball mill, sand mill, and stirred mill; the fineness of the low-temperature carbonized material must meet the D50 of 5-20 μm.

Citation Information

Patent Citations

  • Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN113381016A